Frequency and distribution of lymphoma types in a tertiary care hospital in South India: analysis of 5115 cases using the World Health Organization 2008 classification and comparison with world literature. Issue 5 (May 2013) - Arora, Neeraj; Manipadam, Marie Therese; Nair, Sheila
Abstract This study aimed to analyze the distribution of lymphoid neoplasms in a single tertiary care center in India using the World Health Organization (WHO) 2008 classification. Histological material of 5115 patients with histopathological diagnosis of lymphoma, diagnosed over a period of 10 years (2001–2010), was analyzed retrospectively. Hodgkin lymphoma (HL) constituted 21.3% (n = 1089) and non-Hodgkin lymphomas (NHLs) constituted 78.7% (n = 4026). Of these, B-cell neoplasms accounted for 78.6% (n = 3166) and T-cell/natural killer (NK)-cell neoplasms 20.2% (n = 815) of the NHLs. The commonest subtype of NHL was diffuse large B-cell lymphoma (n = 1886, 46.9%). The frequency of peripheral T-cell/NK-cell lymphomas in this study was higher than in the Western literature but less than the frequency documented in some Asian countries. Similar to the Western literature but in contrast to previous Indian studies, peripheral T-cell lymphoma, not otherwise specified (PTCL NOS) (n = 238) was the commonest histological subtype of T-cell/NK-cell NHL in this study and constituted 5.9% of the total NHLs. Mixed cellularity (MC-CHL) (n = 488, 45%) was the major subtype of HL. Primary extranodal lymphoma (ENL) accounted for 32.8% (n = 1321) of all NHLs and most frequently involved the gastrointestinal tract. This study also documents the frequency of many rare types of lymphoma in South India.